La CSN : 75 ans d'action syndicale et sociale - Ferland, Gilles (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "La CSN : 75 ans d'action syndicale et sociale," edited by Yves Bélanger and Robert Comeau.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z